(NpRAKTI^ESKIJ U^EBNIK gARMONIIs (NtEORIQs - (Nn(B. (Na(B. (NrIMSKIJ (B-(NkORSAKOWs ((NsANKT(B-(NpETERBURGs (NlANXs, 2025)
(NnIKOLAJ aNDREEWI^ rIMSKIJ(B-(NkORSAKOW (B(1844-1908) - (NRUSSKIJ KOMPOZITOR(B, (NPEDAGOG(B, (NDIRIVER(B, (NOB]ESTWENNYJ DEQTELX (B,(NMUZYKALXNYJ KRITIK(B.s
Keywords: (NtEORIQ(B.s